Beberapa Catatan mengenai Perkembangan Antropologi Hukum sebagai Disiplin Akademik di Indonesia - Tapi Ihromi (Antropologi Indonesia, 1989)
This article generally describes the development of legal anthropological studies in Indonesia in the last 20-year period. First, this article proposes some notes concerning a number of papers written by scholars of this discipline as well as writers from other disciplines who are interested in legal anthropology. Second, this article describes teaching of legal anthropology in various universities in Indonesia, and the problems faced by lecturers of this field. Third, the writer provides information on all kinds of research in legal anthropology carried out the Indonesia researchers, and the problems that occurred in the studies and researches on legal anthropology in Indonesia. At the end, the writer specifically focus on important of researches, publication of writings on legal anthropology, and the trainings for legal anthropologist, e.g. through cooperation between Indonesia and foreign universities as a way to stimulate and encourage the development of legal anthropology in Indonesia.